An updated mortality risk analysis of the post-pubertal undescended testis - Shah, Ankur; Feustel, Paul J.; Knuth, Jennifer; Welliver, Charles (Canadian Urological Association Journal, 2018)
Introduction: The undescended testicle (UDT) presents a problem in post-pubertal (PP) men, as it carries an increased risk of developing a germ cell tumour (GCT). Management of the PP patient with an UDT must weigh the relative risk (RR) of perioperative mortality (POM) from orchiectomy against the lifetime risk of death from a GCT. Methods: The most recent data on GCT mortality were obtained from the National Centre for Health Statistics. Standard life tables were used to calculate the cumulative risk over a man’s lifetime based on age. The increased RR of GCT in men with UDT was determined by weighing the observed and expected rates from literature review. Life table data was then multiplied by the RR to define the risk of GCT in men with UDT. Data from patients undergoing similar risk surgical procedures, stratified by American Society of Anesthesiologists (ASA) class, was used to determine POM. Results: Lifetime risk of dying from GCT decreases with increasing age. POM exceeded risks of death from GCT for men after age 50.2 for ASA class 1 and age 35.4 for ASA class 2. Men with an ASA class higher than 2 have a higher risk of POM compared to GCT for all ages. Conclusions: We found different ages from previous reports at which observation is advised. We consider prophylactic orchiectomy only in men who are under 50.2 years if ASA class 1 and under 35.4 years if ASA class 2. Men with an ASA class 3 or higher should always undergo observation.